Measuring Time, Making History - Lynn Hunt (Central European University Press, 2008)
Time is the crucial ingredient in history, and yet historians rarely talk about time as such. These essays offer new insight into the development of modern conceptions of time, from the Christian dating system (BC/AD or BCE/CE) to the idea of "modernity" as a new epoch in human history. Are the Gregorian calendar, world standard time, and modernity itself simply impositions of Western superiority? How did the idea of stages of history culminating in the modern period arise? Is time really ac...